Some properties of a new D-π-A dye based on hydroxyl-methoxybenzene donor and isophorone acceptor moiety: Effects of anion, ethylamine and temperature - Oh, Byeong M.; Noh, Ha Lim; Gwon, Seon Yeong; Park, Young Ki; Cho, Namchul; Lee, Woosung; Kim, Sung Hoon; Kim, Jong H. (Dyes and Pigments, 2018)
Some sensing properties of a new D-π-A dye (dye3) based on hydroxyl-methoxybenzene donor and isophorone acceptor moiety were investigated by using spectroscopic and electrical measurements. The effects of anion, ethylamine and temperature on the color/emission changes of dye3 in solution and resistance changes in thin-film were evaluated and characterized. Dye3 exhibited colorimetric and fluorometric changes in response to cyanide anion. The reversible colorimetric sensing mechanism of dye3 to the cyanide, based on the complex formation by anion binding, was studied with the use of 1H NMR analyses together with theoretical calculations. Then the interactions of dye3 with three ethylamines (mono-, di-, and tri-ethylamine) were investigated. Dye3 showed different degree of changes in UV/Vis absorption spectra when exposed to different ethylamines. From the kinetic studies based on the association constant calculation and theoretical calculations, we revealed that different interaction distance between dye3 and ethylamines caused discrepancy in absorption spectrum changes. Finally, the effect of temperature on the electrical properties of dye3 was explored. Dye3 showed an increase or decrease in electrical resistance because of its semiconducting property. In this article, some unique properties of D-π-A-type dye3 were systemically investigated, and these properties suggest the potential applicability of dye3 to the multi-stimuli (anion, volatile organic compounds (VOCs) and temperature) responsible smart chemosensors.
Keywords: Chemosensor; Effect of temperature; Electrical measurement; Electrical resistances; Ethylamine; Isophorones; Semi-conducting property; Theoretical calculations; Chemosensor; Cyanide; D-π-A isophorone dye; Density functional theory calculation; Ethylamine; Temperature